The Influence of ESG Performance on Firm Value with Cash Holding as a Moderating Variable - Dinarjito, Agung (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The impact of Environmental, Social, and Governance (ESG) performance on firm value as measured by market value is investigated in this study using cash holdings as a moderating variable. The study focuses on non-financial companies that were listed on the Indonesia Stock Exchange between 2020 and 2023. 30 businesses were selected as the final sample following 120 observations over a four-year period. The data came from secondary sources, including financial reports and Bloomberg, and were then analyzed using panel data regression. The findings show that cash holdings do not directly affect business value, and overall ESG performance does not significantly affect firm value. Environmental performance has no discernible impact on company value, while social and governance performance are the only ESG components that have a positive link. Moreover, neither the association between environmental performance and company value nor the overall ESG–firm value relationship is moderated by cash holdings. Cash holdings do, however, increase the impact of governance and social performance on corporate value. These results suggest that when assessing investment decisions, stakeholders and investors may find it advantageous to take into account various facets of ESG performance, especially social and governance dimensions, as well as corporate liquidity in the form of cash reserves. In turn, this may motivate businesses to strategically implement ESG practices in order to boost company value.